Simplify the polynomial (4n² + 3n – 5) − (2n² + 3n
-
+ 6)
1 answer:
Answer:
2n² + 1
Step-by-step explanation:
Given polynomial:
(4n² + 3n – 5) − (2n² + 3n - 6)
Solution:
Removing parentheses,we obtain
Combine like terms:
Done!
Order:BPEMDAS
You might be interested in
What pattern are you talk about
270 solve that yourself lol
BAF and FAD is the answer
Answer:
im pretty sure its C. X=4 but im not positive.
Answer:
17 hours
Step-by-step explanation:
$136/8hr = $17 dollars an hour
$17/hr=$289/t
$17/hr t=$289
t=17 hours